A Novel Fuzzy Neuro Deep Neural Network Model (FNDNN) for Classification of COPD Severity Levels. - Patil, Charushila; Chaware, Anita (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In recent years, there has been an increase in the mortality rate due to lung diseases like Chronic Obstructive Pulmonary Disease (COPD), and it is estimated that it will increase in upcoming years. The majority of deaths (80%) occurred in most of the nations having low and middle income hence, there is a need for a system that can help to reduce the mortality rate by providing proper treatment to the needy patient. Deep learning has shown outstanding performance in solving many real life problems in the healthcare domain. But it does not handle uncertain data. Its black box nature imposes restrictions on understanding its structure. In this study, a novel optimized fuzzy neuro deep-learning approach called FNDNN is proposed for classification. The main idea is the fusion of fuzzy logic and DNN model to deal with data uncertainty and rule extraction. To overcome overfitting of model different techniques like cross fold validation, changing learning rate is applied but the best result is achieved using L2 regularization. Pre-training and optimizing methods for learning parameters of the FNDNN are proposed. The proposed model for classification of COPD severity levels has better performance as compared with other classifiers as shown in results. This FNDNN model is very beneficial to the society and healthcare providers to accurately diagnose the severity levels of COPD and serve the emergency treatment to the needy one. .